2012
DOI: 10.1101/cshperspect.a006171
|View full text |Cite
|
Sign up to set email alerts
|

The Neuropsychological Profile of Alzheimer Disease

Abstract: Neuropsychological assessment has featured prominently over the past 30 years in the characterization of dementia associated with Alzheimer disease (AD). Clinical neuropsychological methods have identified the earliest, most definitive cognitive and behavioral symptoms of illness, contributing to the identification, staging, and tracking of disease. With increasing public awareness of dementia, disease detection has moved to earlier stages of illness, at a time when deficits are both behaviorally and pathologi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
282
0
17

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 456 publications
(334 citation statements)
references
References 199 publications
(243 reference statements)
14
282
0
17
Order By: Relevance
“…31 Thus, produced in response to Ab , LCN2 can regulate important mechanisms and pathways that are critical for brain cell activation 31,32 and that may ultimately lead to alterations in brain areas involved in cognition and memory, which are affected in AD. 46 In agreement, patients with mild cognitive impairment present high levels of LCN2 in the plasma 47 and low levels of LCN2 in the CSF, 8 which points to an imbalance of LCN2 levels in the brain in the early phases of dementia. It is clear, thus, that the role of LCN2 in neurodegenerative disorders such as AD warrants further investigation.…”
Section: Discussionmentioning
confidence: 67%
“…31 Thus, produced in response to Ab , LCN2 can regulate important mechanisms and pathways that are critical for brain cell activation 31,32 and that may ultimately lead to alterations in brain areas involved in cognition and memory, which are affected in AD. 46 In agreement, patients with mild cognitive impairment present high levels of LCN2 in the plasma 47 and low levels of LCN2 in the CSF, 8 which points to an imbalance of LCN2 levels in the brain in the early phases of dementia. It is clear, thus, that the role of LCN2 in neurodegenerative disorders such as AD warrants further investigation.…”
Section: Discussionmentioning
confidence: 67%
“…In the literature 9 , it is widely recognized that early AD patients exhibit non-episodic memory deficits as well, which would involve brain structures other than the MTL. Additional work is required to examine mechanisms underlying cognitive impairments in these other types of memories.…”
Section: Main Textmentioning
confidence: 99%
“…The underlying mechanism of memory failure in early AD patients may not necessarily parallel the molecular and circuit impairments observed in mouse models of early AD. For instance, some early AD patients can exhibit amyloid plaque deposition years before the onset of cognitive decline 9 . However, converging data on the underlying mechanism for genetically-and pharmacologicallyinduced amnesia in animal models increase the possibility that similar memory retrievalbased failures may also operate in an early stage of AD patients.…”
Section: Main Textmentioning
confidence: 99%
“…18 progression to ad (figure 2) 19 Several authors observed an increased rate of progression toward dementia in patients with MCI. 8,[20][21][22][23][24][25] However, studies have not been replicated by other researchers. One explanation for this fact may arise from the observation that memory complaints appear to have little correlation with the performance of individuals on objective cognitive tests.…”
Section: Epidemiologymentioning
confidence: 99%